ECONOMIC JOURNAL OF EMERGING MARKETS : Provincial corruption and local development bank performance - Murharsito, Fitri Ella Fauziah, Emanuel Kristijadi, Rr. Iramani (Fak. Ekonomi UII, 2017)
This paper investigates the effect of provincial corruption on the performance of local development bank, specifically to the profitability and credit quality. We use the data of 26 local development banks in 2012 and 2013. For the provincial corruption measurement we use â€œPublic Institution Openness Indexâ€. Results of this study are first, corruption significantly has a negative effect on the profitability of local development bank. Second, corruption doesnâ€™t affect the credit quality of local development bank. These results are expected to enrich the within country corruption effect to the economic studies, particularly to the local development bank which is infrequently investigated.